Pharmaceutical Humanities and Narrative Pharmacy: An Emerging New Concept in Pharmacy - Mita Banerjee; Thomas Efferth (Pharmaceuticals)
The complexity of our life experiences and the rapid progress in science and technology clearly necessitate reflections from the humanities. The ever-growing intersection between science and society fosters the emergence of novel interdisciplinary fields of research. During the past decade, Medical Humanities arose to meet the need to unravel hidden information beyond technology-driven and fact-based medicine. In the present paper, we put forward the hypothesis that there is a similar requirement to develop Pharmaceutical Humanities as an academic discipline within pharmacy and pharmaceutical biology. Based on Thomas Kuhn’s epistemological theory on the structure of scientific revolutions, one may argue that a paradigm change for Pharmaceutical Humanities might open new levels of insight. Many complex diseases (e.g., cancer, neurological diseases, and mental disorders) remain uncurable for many patients by current pharmacotherapies, and the old beaten paths in our therapeutic thinking may at least partly have to be left behind. By taking examples from Pharmaceutical Biology, we attempt to illustrate that the transdisciplinary dialogue with the humanities is fertile ground not only for enlarging our understanding of disease-related conditions but also for exploring new ways of combatting diseases. In this context, we discuss aspects related to traditional herbal medicine, fair access and benefit sharing of indigenous knowledge about medicinal plants, post-traumatic stress syndrome, the opioid crisis, stress myocardiopathy (broken heart syndrome), and global environmental pollution with microplastics. We also explore possibilities for a narrative turn in pharmacy. The urgent need for inter- and transdisciplinary solutions to pressing health-related problems in our society may create a scholarly atmosphere for the establishment of Pharmaceutical Humanities as a fruitful terrain to respond to the current demands of both science and society.